International Symposium on Photoelectronic Detection and Imaging 2013: Laser Sensing and Imaging and Applications 2013
DOI: 10.1117/12.2034724
|View full text |Cite
|
Sign up to set email alerts
|

Damage effect on CMOS detector irradiated by single-pulse laser

Abstract: ABSTRCTImaging systems are widespread observation tools used to fulfill various functions such as recognition, detection and identification. These devices such as CMOS and CCD can be damaged by laser. It is very important to study the damage mechanism of CMOS and CCD. Previous studies focused on the interference and damage of CCD. There were only a few researches on the interaction of CMOS and the laser.In this paper, using a 60ns, 1064 nm single-pulse laser to radiate the front illuminated CMOS detector, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…This section provides a set of simulations to assess the antilaser damage performance of the wavefront coding imaging system based on the CPP. When CMOS and CCD work, they receive light through the photosensitive surface to generate a photoelectric effect, and the optical signal is converted into an electrical signal [19] . When the irradiation light intensity is excessive, CMOS and CCD may be saturated or even damaged.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…This section provides a set of simulations to assess the antilaser damage performance of the wavefront coding imaging system based on the CPP. When CMOS and CCD work, they receive light through the photosensitive surface to generate a photoelectric effect, and the optical signal is converted into an electrical signal [19] . When the irradiation light intensity is excessive, CMOS and CCD may be saturated or even damaged.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Usually short pulsed lasers are preferred to cause damage due to a lower energy density need, but CW laser may also be efficient if the laser power is high enough. Taking CCD or CMOS camera as examples damage levels have been investigated by Schwartz and Guo [ 31,32]. Pulsed laser line damage levels were in the range 0.5 J/cm 2 for CCD and 10-40 J/cm 2 for CMOS cameras.…”
Section: Jitter and Scintillation Influence On Detector Damagementioning
confidence: 99%
“…The article provides an interesting investigation into the damage morphology. Guo et al performed LIDT measurements on CMOS sensors using a 1064 nm pulsed laser and found the damage threshold to be 0.38 Jcm −2 , with varying degrees of line damage starting between 0.64 and 1.0 Jcm −2 [ 7 ]. …”
Section: Introductionmentioning
confidence: 99%